Does columelloplasty affect the outcome of septal surgery? - Khan, Zeshma Ijaz; Khan, Imran Mohib (Journal of the Pakistan Medical Association, 2025)
Caudal septal deviations and/or dislocations are tricky to deal with; hence patients who had undergone a columelloplasty during their septal surgery using Mohib’s Suture—the surgeon’s own technique—which is a variation of the techniques already in practice, were reviewed for outcome. Data was collected using medical records of the patients. A total of 450 patients who had septal surgeries were taken into account. Their surgical notes were reviewed, and 55 patients who had columelloplasty done during their septal surgery between 2017 and 2023 were included in the study. Information such as their age, gender, and indications for columella surgery was recorded. The patients were contacted and asked for reviews. Results were compiled in a spreadsheet, and basic analysis was done. Out of the 33 patients who responded, 23 had positive feedback, 66.67% patients responded positively to septo-columelloplasty, not only adding to the patients’ relief of symptoms but also aesthetically refining their nasal appearance. Keywords: Columella, Nasal septum, Caudal, Dislocation.